Randomized clinical trial comparing long‐term quality of life for Billroth I versus Roux‐en‐Y reconstruction after distal gastrectomy for gastric cancer. Issue 4 (3rd February 2016) - Nakamura, M.; Nakamori, M.; Ojima, T.; Iwahashi, M.; Horiuchi, T.; Kobayashi, Y.; Yamade, N.; Shimada, K.; Oka, M.; Yamaue, H.
Abstract: Background: Patients' quality of life (QoL) deteriorates remarkably after gastrectomy. Billroth I reconstruction following distal gastrectomy has the physiological advantage of allowing food to pass through the duodenum. It was hypothesized that Billroth I reconstruction would be superior to Roux‐en‐Y reconstruction in terms of long‐term QoL after distal gastrectomy. This study compared two reconstructions in a multicentre prospective randomized clinical trial to identify the optimal reconstruction procedure. Methods: Between January 2009 and September 2010, patients who underwent gastrectomy for gastric cancer were randomized during surgery to Billroth I or Roux‐en‐Y reconstruction. The primary endpoint was assessment of QoL using the Functional Assessment of Cancer Therapy – Gastric (FACT‐Ga) questionnaire 36 months after surgery. Results: A total of 122 patients were enrolled in the study, 60 to Billroth I and 62 to Roux‐en‐Y reconstruction. There were no differences between the two groups in terms of postoperative complications or mortality, and no significant differences in FACT‐Ga total score ( P = 0·496). Symptom scales such as epigastric fullness (heaviness), diarrhoea and fatigue were significantly better in the Billroth I group at 36 months after gastrectomy (heaviness, P = 0·040; diarrhoea, P = 0·046; fatigue, P = 0·029). The rate of weight loss in the third year was lower for patients in the Billroth I group ( P = 0·046). Conclusion: The choice of anastomotic reconstruction after distal gastrectomy resulted in no difference in long‐term QoL in patients with gastric cancer. Registration number: NCT01065688 (http://www.clinicaltrials.gov ). Abstract : No difference between reconstructions